STRATEGI PEMBELAJARAN DALAM MATA KULIAH MATERI DAN PEMBELAJARAN FIQH DI MADRASAH FITK IAIN CURUP - komarudin, Komarudin; Dwi Ratnasari; Asri Karolina (An-Nahdlah: Jurnal Pendidikan Islam, 2022)
The purpose of this study was to determine the learning strategies of lecture material and fiqh learning at the Islamic State Islamic University Curup Madrasah, Curup Utara District, Rejang Lebong Regency, Bengkulu. The subject of this research is the teacher of Fiqh material and learning at the Madrasah IAIN Curup. Data collection uses the methods of observation, interviews and documentation. Data analysis techniques are data reduction, data presentation and conclusion drawing, withdrawal/verification. Checking the validity of the data using triangulation techniques. Based on the results of the study, the strategies used in Fiqh learning at IAIN Curup, North Curup District, Rejang Lebong Regency, Bengkulu, are expository learning strategies, inquiry learning strategies, problem solving learning strategies and active/interactive learning strategies, cooperative learning strategies. at IAIN Curup. The teacher's effort to deal with the problems faced in the Fiqh learning process is to complete the facilities or learning media and choose the right level of learning according to the student's condition.